Factors Associated with Vitamin D Deficiency and Their Relative Importance among Indian Adolescents: An Application of Dominance Analysis - Akif Mustafa; Chander Shekhar (International Journal of Endocrinology, 2023)
Vitamin D deficiency is a serious issue in developing nations, including India. This study investigates the determinants of vitamin D deficiency among Indian adolescents and assesses their relative importance using dominance analysis. Data from the Comprehensive National Nutrition Survey (CNNS) conducted between 2016 and 2018 were utilized in this study. Vitamin D levels were assessed based on serum 25-hydroxyvitamin D concentration, with a sample size encompassing 13,065 adolescents aged between 10 and 19 years. Backward stepwise multivariate logistic regression was used to identify the correlates of vitamin D deficiency, and the relative importance of these factors was assessed using dominance analysis. The study identified nine predictors that were significantly associated with vitamin D deficiency at a 1% level of significance (α = 0.001). Among these factors, sex was found to be the most significant predictor, with female adolescents being 2.66 (95% CI: 95% CI: 2.39–2.96) times more likely to be vitamin D deficient compared to male adolescents. Lifestyle and behavioral factors, such as “sex,” “wealth index,” and “place of residence,” were more dominant in predicting vitamin D deficiency than biological indicators like “BMI” and “serum creatinine.” This underscores the vital role of sunlight exposure in maintaining sufficient vitamin D levels. In summary, this study sheds light on the multifaceted factors contributing to vitamin D deficiency among Indian adolescents, emphasizing the significance of targeted interventions and public health awareness campaigns to mitigate this pressing issue.